BIBLIO Craft :A Modern Crafter's Guide to Using Library Resources to Jumpstart Creative Projects - Pigza, Jessica, (stc craft/a melanie falick book, 2014)
This text teaches readers how to locate library resources to bring their creative ideas to fruition. The author shares her hunting and gathering tips with creatives of all types, informing on how to access inspiring resources online and in person, such as historic watermarks and millinery instructions or Japanese family crests, both online and in person. She also showcases the work of artists who have collaborated with her.